Electroacupuncture inhibits dendritic spine remodeling through the srGAP3-Rac1 signaling pathway in rats with SNL - Qiaoyun Wu; Chenchen Cai; Xinwang Ying; Yujun Zheng; Jiaying Yu; Xiaoxue Gu; Wenzhan Tu; Xinfa Lou; Guanhu Yang; Ming Li; Songhe Jiang (Biological Research, 2023)
Abstract Previous studies have shown that peripheral nerve injury can lead to abnormal dendritic spine remodeling in spinal dorsal horn neurons. Inhibition of abnormal dendritic spine remodeling can relieve neuropathic pain. Electroacupuncture (EA) has a beneficial effect on the treatment of neuropathic pain, but the specific mechanism remains unclear. Evidence has shown that slit-robo GTPase activating protein 3 (srGAP3) and Rho GTPase (Rac1) play very important roles in dendritic spine remodeling. Here, we used srGAP3 siRNA and Rac1 activator CN04 to confirm the relationship between SrGAP3 and Rac1 and their roles in improving neuropathic pain with EA. Spinal nerve ligation (SNL) was used as the experimental model, and thermal withdrawal latency (TWL), mechanical withdrawal threshold (MWT), Western blotting, immunohistochemistry and Golgi-Cox staining were used to examine changes in behavioral performance, protein expression and dendritic spines. More dendritic spines and higher expression levels of srGAP3 were found in the initial phase of neuropathic pain. During the maintenance phase, dendritic spines were more mature, which was consistent with lower expression levels of srGAP3 and higher expression levels of Rac1-GTP. EA during the maintenance phase reduced the density and maturity of dendritic spines of rats with SNL, increased the levels of srGAP3 and reduced the levels of Rac1-GTP, while srGAP3 siRNA and CN04 reversed the therapeutic effects of EA. These results suggest that dendritic spines have different manifestations in different stages of neuropathic pain and that EA may inhibit the abnormal dendritic spine remodeling by regulating the srGAP3/Rac1 signaling pathway to alleviate neuropathic pain.